Peran Karakteristik Pekerjaan Terhadap Prestasi Kerja Yang Dimediasi Oleh Motivasi: Studi Pada Pegawai Dinas Inspektorat Daerah Kabupaten Sampang - Mufarrohah Mufarrohah; Chamariyah Chamariyah; Subijanto Subijanto (Journal of Management and Creative Business, 2024)
Mufarrohah, 2023. The Role of Job Characteristics on Work Performance Mediated by Motivation (Study of Sampang Regency Regional Inspectorate Service Employees). Wijaya Putra University Postgraduate Program Surabaya. This type of research is explanatory research, the approach used is a quantitative approach, the research sample is 34 people. The analysis tool uses Smart PLS (Partial Least Square). Research objectives: 1) To describe the job characteristics, motivation and work performance of employees at the Sampang Regency Regional Inspectorate Service. 2) To test and analyze the direct influence of job characteristics on employee work performance at the Sampang Regency Regional Inspectorate Service. 3) To test and analyze the direct influence of work ability on employee motivation at the Sampang Regency Regional Inspectorate Service. 4) To test and analyze the direct influence of motivation on employee work performance at the Sampang Regency Regional Inspectorate Service. 5) To test and analyze the significant indirect influence of job characteristics on employee work performance at the Sampang Regency Regional Inspectorate Service which is mediated by motivation. The research results show that: 1) Job characteristics have an insignificant effect on work performance with a p value of 0.100. 2) Job characteristics have a significant effect on motivation with a p value of 0.000. 3) Motivation has a significant effect on work performance with a p value of 0.000. 4) Job characteristics have a significant effect on work performance which is mediated by motivation with a p value of 0.007.